Differences in Perception among Teachers about Rashtriya Madhyamik Shiksha Abhiyan in West Bengal - Das, Premendra; Deb, Prasenjit (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
Teachers are most significant factor in education system. Teachers are playing very important role for the success of education system. That system of education may be for primary level or for secondary level, or it may be for level of higher education. Teachers are dynamic and conscious factor of education, they are very cognizant about every phenomena of education due to their professional competence. They are well acquainted with national literacy mission, post literacy mission, district primary education programmer and Sarva Shiksha Mission. Recently launched new programmer of secondary education as Rashtriya Madhyamik Shiksha Abhiyan, this study had concentrated to identify the differences of the level of perception about Rashtriya Madhyamik Shiksha Abhiyan (RMSA) among the school teachers, in term of 17 variables viz. Age of respondent (X1), Educational qualification of respondent (X2), Number of family members (X3), Number of children going to school (X4), Number of Children studying in class IX and X (X5), Need of private tuition (X6), Reasons behind the private tuition (X7),Â  Additional boost up given by RMSA (X8), Shortfall of present secondary education system (X9), Remediable steps of secondary education (X10), Awareness of social facts (X11) Involvement in social activities (X12), Influence of SSA (X13), Achievement of SSA (X14), Functions of Mid-day Meal(X15), Initiation of Mid-day Meal for Secondary level (X16), and Better options ofÂ  implementation of Mid-day Meal(X17) were found to bear mentionable impact on the high and low level of perception (Y) of the school teachers of West Bengal.